Peran Pembelajaran PAI Dalam Memperkuat Multikulturalisme di Masyarakat - Suchy Octarilza, Adisti; Irfan Zaenuri, Muhammad; Mubin, Nurul (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2024)
Multiculturalism teaches us to appreciate diversity and recognizes that everyone has the right to be respected regardless of their cultural and religious background. Multicultural PAI learning can help students internalize universal values ​​such as tolerance, justice and unity. With an inclusive approach, PAI can become a bridge for dialogue between religions and cultures, reducing the possibility of conflict that may occur due to differences. This research analyzes the role of PAI teachers in implementing multiculturalism education, as well as the possible challenges they face. By understanding the role of multiculturalism, it is hoped that multicultural education can be implemented more effectively, producing a more tolerant and open generation.